The Widely Used Antihelmintic Drug Albendazole is a Potent Inducer of Loss of Heterozygosity - Will Castro, Luiza S. E. P.; Pieters, Wietske; Alemdehy, Mir Farshid; Aslam, Muhammad A.; Buoninfante, Olimpia Alessandra; Raaijmakers, Jonne A.; Pilzecker, Bas; van den Berk, Paul C. M.; te Riele, Hein; Medema, René H.; Pedrosa, Rozangela C.; Jacobs, Heinz (Frontiers in Pharmacology, 2021)
The antihelminthic drug ABZ and its metabolites belong to the chemical family of benzimidazoles (BZM) that act as potent tubulin polymerization inhibitors, suggesting a potential re-direction of BZMs for cancer therapy. Applying UV-Vis spectrometry we here demonstrate ABZ as a DNA intercalator. This novel insight led us to determine the primary mode of ABZ action in mammalian cells. As revealed by RNA sequencing, ABZ did not grossly affect replication as analyzed by survival and replication stress signaling, nor transcription. Actually, this unbiased transcriptome analysis revealed a marked cell cycle signature in ABZ exposed cells. Indeed, short-term exposure to ABZ arrested mammalian cells in G2/M cell cycle stages, associated with frequent gains and losses of chromatin. Cell biological analysis revealed ABZ as a potent mammalian spindle poison for normal and malignant cells, explaining the serious chromosome segregation defects. As chromosomal aberrations promote both cancer development and cell death, we determined if besides its general cytotoxicity, ABZ could predispose to tumor development. As measured by loss of heterozygosity (LOH) in vitro and in vivo ABZ was found as a potent inducer of LOH and accelerator of chromosomal missegregation.